THE PHENOMENON OF NEOLOGIZATION IN THE POETRY AND PROSE OF UKRAINIAN FUTURISTS: CREATION OF A CORPUS OF TEXTS AND AUTOMATION OF LEXICAL NOVELTY MINING - NAKHLIK, Olesya; KOLESNYK, Yehor (Linguistic and Conceptual Worldviews, 2024)
This article is dedicated to the analysis of the activity of neologization processes in the works of Ukrainian futurists. The movement's ideological underpinnings, which served as a catalyst for linguistic experimentation within the movement, are briefly discussed. Additionally, the article provides a concise historical overview of Ukrainian futurism and its broader historical context. A critical concern addressed in this study is the need to augment the corpus of Ukrainian futurist texts to facilitate further research in this area.The research offers a comprehensive spectrum of neologisms that have been formed through various methods and have been employed across diverse literary genres within the context of Ukrainian futurism. Specifically, it formulates criteria based on the absence of identified terms in prominent linguistic references, such as the “Large Electronic Dictionary of Ukrainian” and the “Dictionary of the Ukrainian language” in 11 volumes, and the “Dictionary of the Ukrainian language” published in 1909. Moreover, the inclusion criteria involve the limited occurrence of neologisms in the "General Regionally Annotated Corpus of Ukrainian," with a focus on distinguishing futurist works from those of non-futurist authors, exemplified by the comparative analysis of futurist writers and Mike Johansen.Furthermore, the study delves into the methods employed to automate the extraction of these neologisms, showcasing both their advantages and disadvantages in the realm of linguistic research. A crucial aspect of the study involves a quantitative analysis of the frequency of neologisms in the works of futurist writers and Mike Johansen. This comparative analysis aims to unveil characteristic features of word formation within futurist literature. Through practical demonstrations, the study enhances our understanding not only of the linguistic nuances within Ukrainian futurism but also of the broader implications of utilizing automated approaches in the study of linguistic evolution and innovation.
Keywords: Ukrainian futurism, computer lexicography, neologism, text corpus